POLICY ON OVERCOMING VILLAGE BUDGET DEVIATIONS BY THE GOVERNMENT INTERNAL SUPERVISORY APPARATUS IN INDONESIA (CASE STUDY OF TANJUNGSARI VILLAGE, LAMPUNG) - I Ketut Seregig; Bambang Hartono; Yustina Ndari (Cepalo, 2021)
Corruption is deeply rooted in Indonesia. This fact is undeniable when this crime has occurred at the lowest government level, namely in the village government. One sample of cases raised in this study is the alleged Corruption Crime committed by the Head of Tanjungsari Natar Village, South Lampung, named Robangi. The problems examined in this alleged criminal act are the factors causing the perpetrator to commit the criminal act of corruption. Second, the pattern of countermeasures carried out by APIP in resolving the case. The method used is qualitative and in the research data collection using a normative juridical approach and empirical juridical. Meanwhile, the theory used as a knife of analysis is the theory of Non-Penal Policy proposed by Muladi and Barda Nawawi Arief, which states that "non-penal policy is the prevention of crime which prioritizes the prevention of crimes committed by guidance, aims to prevent before the crime occurs, and/or the perpetrator does not repeat his actions".The results showed that the factors causing the perpetrator to commit these acts were because the project implementation was not following the proposal, the use of funds was not per the project proposal (total loss), the reason was that at the request of the community, the planned construction was moved to another place. This act is procedurally violating the SOP for the management of state finances. However, empirical facts prove no state loss in the corruption crime allegedly committed by the village head. Based on these facts, APIP South Lampung Regency has implemented a countermeasures policy by imposing administrative sanctions on the village head of Tanjungsari, Natar District, South Lampung.